Genetic variations of the L2 gene in human papillomavirus (HPV) type 16 from cervical cancer patients in Sumatra region, Indonesia - Savira, Maya; Farniga, Arnaldi; Ilmiah, Zidny; Rachmadina, Rachmadina; Rini, Ika A.; Kemal, Rahmat A.; Mahargyarani, Azza E.; Admiral, Muhammad Z.; Sofian, Amru; Razali, Renardy R.; Suhaimi, Donel; Putra, Andani E. (Narra Sains Indonesia, 2025)
The L2 protein, a minor capsid component of human papillomavirus (HPV), plays a critical role in the HPV life cycle by packaging the viral genome with the L1 protein and facilitating DNA transport to the nucleus. Identifying genetic variations in the L2 gene is essential for improving vaccine development, diagnostic accuracy, and understanding viral evolution, potentially contributing to more effective HPV vaccines. The aim of this study was to investigate the genetic variation of the L2 gene in cervical cancer specimens collected from patients in Riau Province, Indonesia. A single-center, cross-sectional study was conducted at Arifin Achmad General Hospital, Riau Province, involving cervical cancer patients with confirmed HPV16 infection between January 2018 and August 2020. Demographic, clinical, and risk factor data were collected through structured interviews and direct assessments. Cervical biopsy specimens were collected, and viral DNA was extracted for L2 gene amplification using polymerase chain reaction (PCR). Sequencing was conducted on PCR products, followed by single-nucleotide polymorphism (SNP) identification through alignment with the HPV16 reference genome. The amplification and sequencing of the HPV16 L2 gene from 22 cervical cancer specimens revealed 36 SNPs, including 31 nonsynonymous and five synonymous mutations. High-frequency mutations were observed at nucleotide positions 4,074 and 4,177, each detected in 95.45% of the samples. Notable insertions were found at positions 3,668–3,669 and 4,275–4,276, indicating substantial sequence variation. Phylogenetic analysis grouped the sequences into three clusters, with most belonging to sub-lineage A2 (European), while others aligned with A4 (Asian) and East Asian lineages. The observed genetic diversity in the HPV16 L2 gene may reflect regional viral evolution and has potential implications for future vaccine development.